Carrying Out Rapid Qualitative Research During a Pandemic: Emerging Lessons From COVID-19. (December 2020) - Vindrola-Padros, Cecilia; Chisnall, Georgia; Cooper, Silvie; Dowrick, Anna; Djellouli, Nehla; Symmons, Sophie Mulcahy; Martin, Sam; Singleton, Georgina; Vanderslott, Samantha; Vera, Norha; Johnson, Ginger A.
Social scientists have a robust history of contributing to better understandings of and responses to disease outbreaks. The implementation of qualitative research in the context of infectious epidemics, however, continues to lag behind in the delivery, credibility, and timeliness of findings when compared with other research designs. The purpose of this article is to reflect on our experience of carrying out three research studies (a rapid appraisal, a qualitative study based on interviews, and a mixed-methods survey) aimed at exploring health care delivery in the context of COVID-19. We highlight the importance of qualitative data to inform evidence-based public health responses and provide a way forward to global research teams who wish to implement similar rapid qualitative studies. We reflect on the challenges of setting up research teams, obtaining ethical approval, collecting and analyzing data in real-time and sharing actionable findings.